2013
DOI: 10.1182/blood.v122.21.3043.3043
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With Rituximab Monotherapy Versus R-CHOP In Post-Transplant Lymphoproliferative Disease Arising After Solid Organ Transplant: A Multicentre UK Study

Abstract: Post-transplant lymphoproliferative disease (PTLD) remains an important complication of solid organ transplantation. For B-cell PTLD, current first line therapies are Rituximab monotherapy (R-Mono) or R-CHOP. However, optimal selection of initial treatment is challenging due to concerns about the relative efficacy and toxicity of these modalities, and because of uncertainty about the prognostic value of baseline factors. This retrospective study identified 72 biopsy-proven cases of PTLD, diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Indeed, given the lack of side effects compared to conventional chemotherapeutic agents (Cruz et al , ) and their apparent efficacy, third party anti‐EBV CTLs may also be indicated in other situations. Although rituximab can be effective for PTLD, the short‐term response rate is only about 60–80% (Messahel et al , ; Burns et al , ; Caillard et al , ; Styczynski et al , ) and the longer‐term prognosis may be worse (Heslop et al , ). Use of CTLs might therefore be considered at an earlier stage in the therapeutic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, given the lack of side effects compared to conventional chemotherapeutic agents (Cruz et al , ) and their apparent efficacy, third party anti‐EBV CTLs may also be indicated in other situations. Although rituximab can be effective for PTLD, the short‐term response rate is only about 60–80% (Messahel et al , ; Burns et al , ; Caillard et al , ; Styczynski et al , ) and the longer‐term prognosis may be worse (Heslop et al , ). Use of CTLs might therefore be considered at an earlier stage in the therapeutic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the perceived efficacy of chemotherapeutic regimens containing rituximab has rendered autologous anti‐EBV CTLs to be considered unviable as a clinical product. Nevertheless, about one‐third of patients with a diagnosis of PTLD continue to die either from PTLD itself or complications of treatment (Burns et al , ; Caillard et al , ; Styczynski et al , ; Uhlin et al , ).…”
Section: Previous Experience Of Third Party Derived Ctls In the Treatmentioning
confidence: 99%